Cytomegalovirus viremia as a risk factor for mortality in HIV-associated cryptococcal and tuberculous meningitis. (September 2022) - Skipper, Caleb P.; Hullsiek, Katherine Huppler; Cresswell, Fiona V.; Tadeo, Kiiza K.; Okirwoth, Michael; Blackstad, Mark; Hernandez-Alvarado, Nelmary; Fernández-Alarcón, Claudia; Walukaga, Stewart; Martyn, Emily; Ellis, Jayne; Ssebambulidde, Kenneth; et al.
Highlights: CMV viremia was found in 36% of persons with HIV-associated meningitis. Greater CMV viral load was positively associated with adjusted 18-week mortality. It is uncertain whether CMV viremia is a marker of immune dysfunction or drives mortality. Randomized controlled trials using CMV antivirals are needed to determine whether CMV is a modifiable risk factor. Abstract: Objectives: CMV viremia is associated with increased mortality in persons with HIV. We previously demonstrated that CMV viremia was a risk factor for 10-week mortality in antiretroviral therapy (ART)-naïve persons with cryptococcal meningitis. We investigated whether similar observations existed over a broader cohort of patients with HIV-associated meningitis at 18 weeks. Methods: We prospectively enrolled Ugandans with cryptococcal or TB meningitis into clinical trials in 2015-2019. We quantified CMV DNA concentrations from stored baseline plasma or serum samples from 340 participants. We compared 18-week survival between those with and without CMV viremia. Results: We included 308 persons with cryptococcal meningitis and 32 with TB meningitis, of whom 121 (36%) had detectable CMV DNA. Baseline CD4 + T-cell counts (14 vs. 24 cells/µl; P = 0.07) and antiretroviral exposure (47% vs. 45%; P = 0.68) did not differ between persons with and without CMV viremia. The 18-week mortality was 50% (61/121) in those with CMV viremia versus 34% (74/219) in those without ( P = 0.003). Detectable CMV viremia (adjusted hazard ratio [aHR] 1.60; 95% confidence interval [CI] 1.13-2.25; P = 0.008) and greater viral load (aHR 1.22 per log10 IU/ml increase; 95% CI 1.09-1.35; P <0.001) were positively associated with all-cause mortality through 18 weeks. Conclusion: CMV viremia at baseline was associated with a higher risk of death at 18 weeks among persons with HIV-associated cryptococcal or TB meningitis, and the risk increased as the CMV viral load increased. Further investigation is warranted to determine whether CMV is a modifiable risk contributing to deaths in HIV-associated meningitis or is a biomarker of immune dysfunction.